REPRESENTASI MASYARAKAT PEDESAAN DALAM NOVEL BEKISAR MERAH KARYA AHMAD TOHARI - Kamarullah, Reza; Hayati, Yenni; Nasution, Bakhtaruddin (Jurnal Bahasa dan Sastra, 2017)
This article aims to describe the representation of rural communities are depicted in Bekisar Merah novel by Ahmad Tohari. This research is a qualitative, descriptive method that aims to create a description, picture, or painting in a systematic, factual, and accurate information on the facts, nature and the relationship between the phenomenon investigated, so saw the quality or the quality of the object under study , Results of the study found that the novel Bekisar Merah by Ahmad Tohari discusses the representation of rural communities, which can be described in six indicators, namely: (1) Process and social interaction in the countryside illustrate the friendliness between people, and solving problems together, (2 ) social stratification in rural areas based on soil and have a backup business ownership development. (3) the family and kinship systems rural communities have a sense of togetherness more closely and they consider the neighbors are family, (4) social change, (5) social organizations at the village bring a positive influence, helpful and is an inevitable requirement, (6) culture (norms and values) still held firm.Keywords: rural communities, representation, novel